The Constitutional Consequences of the Failure of Intra-religious Accommodation in Pakistan: Implications for Religious Liberty in a Religious Nationalist State - Tanchum, Micha’el M. (Journal of law, religion and state, 2013)
This article examines how the failure to defend intra-religious accommodation from sectarian challenges in the public sphere creates structures of political opportunity for religious extremist organizations to exert a constraining influence on positive law-making and individual rights. Through a comparison of the government response to Sunni sectarian agitation during the 1950s and the early 1970s in Pakistan, each time conducted by organizations affiliated with the Deobandi movement (the movement that later created the Taliban in 1994), it will be shown how the failure to uphold intra-religious accommodation impacted the Pakistan’s constitutional development and furthered Pakistan’s shift from liberal democracy to Islamism. The article suggests that a religious discourse of intra-religious accommodation, not a prohibition of religious expression in the public sphere (laïcité), can serve as an important foundation for the development of religious liberty and civil society in newly democratizing Muslim societies.